Analysis of Public Behavior In Investing In Sharia Digitally Through Financial Technology Services Using UTAUT Modification - Asgar, Asgar; Hasbi; Masdathul Ihzani; Nur Rahmi (Jurnal Al-Istishna, 2025)
Sharia investment is increasingly being looked at by people from various circles in Indonesia. This study aims to analyze public behavior in sharia investing through financial technology (fintech) services using a modification of the unified theory of acceptance and use of the technology (UTAUT). This UTAUT theory was chosen because it is a mature theory and has been empirically tested with a strong enough ability to predict the acceptance and use of a technology. This study used quantitative methods. Data collection using questionnaires conducted online through google form. Analysis with Structural Equation Modeling Partial Least Square (SEM-PLS) using the SmartPLS 4 application with a sample of 100 respondents spread across several districts in South Sulawesi. The measurement model uses the outer model and inner model through validity tests and reliability tests as well as structural model measurements in hypothesis tests using prediction models. The results showed that the behavior intention to invest in sharia digitally through fintech services was significantly influenced by sharia decisions, performance expectancy and effort expectancy, and fintech usage adoption was significantly influenced by sharia decisions. However, social influence, facilitating condition on behavior intention and facilitating condition, behavior intention on fintech adoption usage did not have a significant effect